Efeito das variações climáticas ligadas ao ENOS na população de Cissia phronius (Lepidoptera: Satyrinae) no extremo sul do Brasil - Silva, Giovanna Tereza Oliveira da (2020)
Temporal studies with populations have become increasingly necessary for the implementation of conservation actions, especially in tropical and subtropical environments, where there are high rates of degradation and loss of habitat. Among the abundant and multivoltine subtropical insects is Cissia phronius (Godart, 1824), a generalist and common neotropical fruit-feeding butterfly. However, adult individuals have their seasonal patterns, as well as activity and abundance negatively affected by climatic variations, usually resulting from interannual weather events. Therefore, the aim of this work was to analyze patterns of temporal variation in the population dynamics of C. phronius and to relate the effect of the global climatic phenomenon, of an atmospheric-oceanic character, El Niño Southern Oscillation in Restinga forests in the extreme south Brazil. Standardized samplings were carried out for four and a half years. Nine sample units were listed, in fragments of Restinga forest. In each sample unit, five baited traps were installed and reviewed three days a month. The capture-markrecapture method was used to sample the individuals. Climatic indices were checked daily and the monitoring of climatological bulletins was done monthly. A priori analysis was performed combining the abundance data of C. phronius with the absence and/or presence of El Niño Southern Oscillation in order to assess the influence of the phenomenon on population size and to compare the different fluctuation patterns and population decline during periods of presence, positive phase (El Niño) and negative phase (La Niña), and absence of the phenomenon. To investigate which covariate best represent the influence of El Niño Southern Oscillation on the population size of C. phronius, generalized linear models were used in an R environment. The results demonstrate that the phenomenon influences the population size of C. phronius. In La Niña and neutral period there is a population growth and, consequently, greater activity of adult individuals than during El Niño, which indicates population decline. C. phronius has an a correlation of abundance with climatic covariates, especially humidity, and, as a result, their life cycle can be extremely affected by them, especially during El Niño periods. That said, the implications of the presence of El Niño Southern Oscillation are that the survival of the study species is highly sensitive to climatic variations resulting from the phenomenon, and can serve as a model for other neotropical species and this becomes very relevant to these conclusions.